2002
DOI: 10.1021/ma011784j
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Crystal−Amorphous Interphase in Lamellar Semicrystalline Poly(ethylene terephthalate)

Abstract: We report on the direct evidence in real space of the crystal−amorphous interphase in a lamellar semicrystalline polymer, poly(ethylene terephthalate) (PET). This evidence was obtained by the TEM observation of the compositional variation of (stained) PET segments in the boundary of an isolated lamellar stack in a binary blend of semicrystalline PET with amorphous poly(ether imide). The lamellar morphology exhibited by the TEM image of a stained lamellar stack was also investigated in detail, in terms of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 32 publications
(49 reference statements)
1
44
0
Order By: Relevance
“…In general, small angle X-ray scattering (SAXS) is a very suitable tool to study the development of these arrays of lamella [3]. The, either homogeneous or heterogeneous, nature of the distribution of lamellar stacks in the system has been a subject of extended debate in the last years [1,[4][5][6][7][8][9]. Traditionally, the observation of the crystalline phase evolution has been performed by diffraction techniques [10] and by microscopy techniques [11].…”
Section: Introductionmentioning
confidence: 99%
“…In general, small angle X-ray scattering (SAXS) is a very suitable tool to study the development of these arrays of lamella [3]. The, either homogeneous or heterogeneous, nature of the distribution of lamellar stacks in the system has been a subject of extended debate in the last years [1,[4][5][6][7][8][9]. Traditionally, the observation of the crystalline phase evolution has been performed by diffraction techniques [10] and by microscopy techniques [11].…”
Section: Introductionmentioning
confidence: 99%
“…The similarity in inelastic neutron scattering of the semicrystalline and amorphous phases indicates a highly disordered bulk crystal. This disorder is also present at the surface as examined by AFM, transmission electron microscopy, dielectric spectroscopy, and neutron scattering studies, which revealed amorphous-crystal interphases in lamellar stacks of PET (49)(50)(51).…”
Section: Discussionmentioning
confidence: 93%
“…In particular, the existence of interfacial regions with properties lying between those of crystalline and undisturbed amorphous regions has been revealed by quantitative comparisons of the degree of crystallinity, determined by distinct methods [88,89]. Although the existence of the order-disorder transition region at the crystal-amorphous boundaries is well demonstrated, until the recent work of Ivanov and co-workers [90] there was no direct experimental demonstration of the crystal-amorphous interface. This evidence was obtained by transmission electron microscopy (TEM) observation of the compositional variation of stained PET segments in the boundary of an isolated lamellar stack in a binary blend of semicrystalline PET with amorphous poly(ether imide) (PEI) [90].…”
Section: Influence Of Crystallinity On the Glass Transition Dynamicsmentioning
confidence: 99%
“…Although the existence of the order-disorder transition region at the crystal-amorphous boundaries is well demonstrated, until the recent work of Ivanov and co-workers [90] there was no direct experimental demonstration of the crystal-amorphous interface. This evidence was obtained by transmission electron microscopy (TEM) observation of the compositional variation of stained PET segments in the boundary of an isolated lamellar stack in a binary blend of semicrystalline PET with amorphous poly(ether imide) (PEI) [90].…”
Section: Influence Of Crystallinity On the Glass Transition Dynamicsmentioning
confidence: 99%